Participatory planning to conserve freshwater ecosystems in the Rift Valley Lakes Basin, Ethiopia - Mekuria, Wolde; Girma, R.; Haileslassie, Amare; Tegegne, Desalegn; Haile, Alemseged Tamiru (Elsevier, 2024)
Freshwater ecosystems are important for directly ensuring a range of benefits and services that sustain local livelihoods and help mitigate climate change. However, freshwater ecosystems are threatened by anthropogenic and natural pressures affecting their ability to sustainably provide these services. Managing freshwater ecosys tems is mainly challenged by the complexity of the drivers of their degradation and by the difficulty of balancing the need for short-term socioeconomic development and protecting and restoring ecosystems to support longterm, sustainable development. Addressing such challenges requires an integrated and systematic approach, catchment-wide management and meaningful engagement and collaboration among stakeholders. The present study was conducted in Lake Ziway, Rift Valley Lakes Basin, Ethiopia. The overarching objective was to conserve the freshwater ecosystem through co-planning and designing management options for the buffer zone and entire catchment. The study engaged local communities through multiple approaches including inception and vali dation workshops, reconnaissance surveys, key informant interviews and focus group discussions. It also employed quantitative data collection methods to characterize the freshwater ecosystem and entire catchment. The participatory approach employed in this study identified multiple management options including tree-based forest and landscape restoration measures, integrated soil and water conservation, and multiple buffer zone restoration measures. The identified and validated management options are aimed at improving the functionality of the freshwater ecosystem in the face of increased need of economic development and climate change. Furthermore, the study provided key recommendations to support the processes of policy development and the effective implementation of suggested and validated management options.